The Arabic Lexical Layer In Babur’s Baburnama: Semantic And Stylistic Adaptation (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the Arabic lexical layer in Zahiriddin Muhammad Babur’s Baburnama and the semantic and grammatical changes these loanwords underwent in their adaptation to Uzbek. It surveys the historical course of Arabic borrowing into Uzbek, identifies the principal types of semantic and stylistic change (from concrete to abstract meaning, semantic broadening and narrowing, shifts in stylistic register, and the formation of fixed phrases), and classifies the Arabic vocabulary of the Baburnama into thematic groups. The study shows that Arabisms enriched not only the lexicon but also the semantic and grammatical system of the Uzbek language.
Keywords: Baburnama; Zahiriddin Muhammad Babur; Arabic loanwords; lexical- semantic adaptation; semantic broadening; semantic narrowing; thematic groups; Old Uzbek literary language